MAXILLARY FRENECTOMY IN PEDIATRIC PATIENT USING ELECTROCAUTERY TECHNIQUE : REPORT OF 2 CASES - Nurdiana Dewi; Rahmad Arifin; Beta Widya Oktiani (Dentino : Jurnal Kedokteran Gigi, 2023)
Background : The frenum is defined as a mocous membrane fold that attaches the lip and the cheek to the alveolar mucosa, the gingiva and the underlying periosteum.  The unsual frenum need treated by frenectomy or by frenotomy procedure. Conventional technique of frenectomy carries the risks of surgery like bleeding and patient compliance with favorable healing. Electrocautery technique provide bloodless area and clear view of the operative field. Case : The present article is a report of two cases of frenectomy using electrocautery technique. Case management : Maxillary frenectomy of 2 patients was carried out using electrocautery technique after the area was anesthetized with 4% articaine. Continuous saline irrigation was given while using the electrocautery. Minimal bleeding was seen during the procedure. No sutures were placed after the treatment. One week recalled visit showed almost complete healing in both cases. No discomfort was complained by patinet during and after the treatment. Conclusion : Electrocautery is recommended for performing frenectomy due to its effectiveness and safety. The procedure causes light bleeding and does not have postoperative complications. The use of electrocautery in frenectomy provides a reduction in work time as well as greater comfort and safety for the patient dan dentist. Keywords : Frenectomy, Frenum, Pediatric Patient